Chloroform Fraction of Drymaria cordata Linn (CFDC) Suppresses Estradiol Benzoate- Induced Endometrial Hyperplasia - Olowofolahan, Adeola O.; Akinjiola, Oluwatofunmi; Olanlokun, John Oludele; Oyebode, Olubukola Titilope; Aina, Oluwasanmi Olayinka; Olorunsogo, Olufunso Olabode (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: The diagnosis of uterine dysfunction (endometrial hyperplasia) is on the rise. The available treatment is quite expensive and associated with some side effects. The therapeutic potential of natural products is now being explored, as they are easily available with little or no side effects. Drymaraia cordata is folklorically utilized in the treatment of diverse ailments including uterine fibroids. Objectives: This study aims to investigate the potential therapeutic effect of chloroform fraction of methanol extract of Drymaria cordata (CFDC) in estradiol benzoate (EB)-induced endometrial hyperplasia. Methods: Thirty-six rats were randomly divided equally into six groups. These included control group, CFDC: (100 mg/kg), CFDC: (200 mg/kg), EB: (2 mg/kg), EB + CFDC (100 mg/kg), and EB + CFDC (200 mg/kg). Endometrial hyperplasia (EH) was induced by intraperitoneal injection of EB. The levels of estrogen (E2), progesterone (PG), Follicle stimulating hormone (FSH), Luteinizing hormone (LH), Malondialdehyde (MDA), Superoxide dismutase (SOD), and Glutathione peroxidase (GSH-Px) activities were determined using ELISA technique. The uterine histological assessment and immunohistochemical expression levels of estrogen receptor, Ki-67, cytochrome c, and caspase 3 were carried out. Results: EH was severely expressed in the uterine section of EB-treated rats. However, CFDC administration improved the pathological features of the animal model. The sex hormones levels were increased in the EB-treated group, which were significantly reduced by CFDC. The antioxidant indices were also restored by CFDC. Immunoexpression levels of ERα and Ki-67 were downregulated while cytochrome c and caspase 3 were upregulated by CFDC. Conclusion: This study suggests that CFDC contains phytochemicals that can protect against EB-induced EH via modulation of hormonal signaling, apoptotic machinery, and oxidative indices.
Keywords: apoptosis